2020
DOI: 10.3390/molecules25214982
|View full text |Cite
|
Sign up to set email alerts
|

Uvaol Improves the Functioning of Fibroblasts and Endothelial Cells and Accelerates the Healing of Cutaneous Wounds in Mice

Abstract: Uvaol is a natural pentacyclic triterpene that is widely found in olives and virgin olive oil, exerting various pharmacological properties. However, information remains limited about how it affects fibroblasts and endothelial cells in events associated with wound healing. Here, we report the effect of uvaol in the in vitro and in vivo healing process. We show the positive effects of uvaol on migration of fibroblasts and endothelial cells in the scratch assay. Protein synthesis of fibronectin and laminin (but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 52 publications
(57 reference statements)
1
16
0
Order By: Relevance
“…Erythrodiol exhibited antiproliferative and apoptotic effects against adenocarcinoma [44] and promoted the lowering of LDL-cholesterol levels in human blood [45]. Uvaol has been effective in promoting accelerated and improved wound healing [46] and alleviating inflammatory bowel disease in mice [47], while in humans, it has shown antitumor activity [27,48].…”
Section: Other Beneficial Effects Of Sterols and Triterpene Diolsmentioning
confidence: 99%
“…Erythrodiol exhibited antiproliferative and apoptotic effects against adenocarcinoma [44] and promoted the lowering of LDL-cholesterol levels in human blood [45]. Uvaol has been effective in promoting accelerated and improved wound healing [46] and alleviating inflammatory bowel disease in mice [47], while in humans, it has shown antitumor activity [27,48].…”
Section: Other Beneficial Effects Of Sterols and Triterpene Diolsmentioning
confidence: 99%
“…Callus tissue from the stems of A. arguta (Actinidiaceae) produced three ursane-type triterpenes including ursolaldehyde 41, α-amyrin 42, and uvaol 43 [26]. Of them, compound 43 showed anti-inflammatory, anticancer, and wound healing activities [27][28][29]. Antiinflammatory properties of 43 on DSS-induced colitis and LPS-stimulated macrophages have been explored detailly and completely.…”
Section: Ursane Triterpenoidsmentioning
confidence: 99%
“…arguta [ 34 ] Leaves 39 (2 α ,3 β )-2,3,23-Trihydroxyurs-13(18)-en-28-oic acid A. chinensis Planch [ 52 ] Roots 40 Fupenzic acid A . chinensis [ 25 ] Root bark Antiviral (in vitro) [ 25 ] 41 Nrsolaldehyde A. arguta [ 26 ] Stems 42 α -Amyrin A. arguta [ 26 ] Stems 43 Uvaol A. arguta [ 26 ] Stems Anti-inflammatory (in vivo) [ 27 ] Anticancer (in vitro) [ 28 ] Wound healing (in vivo) [ 29 ] 44 Pseudotaraxasterol A. chinensis Planch [ 19 ] Roots 45 2 α ,3 α ,24-Trihydroxyurs-11-en-13,28-olide A. polygama [ 23 ] Fruit galls 46 2 α ,3 β -Dihydroxyurs-12-en-28,30-olide A. chinensis [ 30 ] Roots …”
Section: Chemical Constituentsmentioning
confidence: 99%
“…A number of drugs and health care products that promote wound healing are mainly designed according to the four stages on which intervene, such as hemostatic drugs, antimicrobial drugs, anti-inflammatory drugs or agents that promote collagen synthesis. Recent research demonstrated that the decrease of inflammation and highly orchestrated remodeling could improve the performance of new regenerative skin, and even achieve scarless healing [ 5 , 6 ], and many Chinese herbal medicine and marine bioactivity substances, such as collagen (peptides), have been shown to accelerate skin wound healing and prevent abnormal scar formation [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%